The Skills of Intended Meaning behind the Context when Reading Poetry among Fifth Grade Students- Literary Branch from Teachers’ Perspectives (Journal of the College of Education for Women, 2021)
The current research aims to investigate the skills of the intended meaning beyond the context when reading poetry among fifth literary students. To achieve the aim of the research, the researcher has followed the descriptive approach and used two tools: an open questionnaire that includes an inquiry about the skills of the intended meaning beyond the poetic context, and a closed questionnaire that were examined by the juries, and modified accordingly. Besides, its validity and stability were examined by applying the study on an exploratory sample of (15) teachers to reach its final version and determine the time required to answer it. Then, the researcher applied it on the research sample of (96) male and female teachers selected from various schools in the center of Babylon Governorate, who teach fifth grade of the literary branch. After processing the responses statistically, the research has concluded the following: three intended meaning skills have been identified to determine the intended meaning beyond the poetic context. Regarding the item (training students to be able to determine the meaning of difficult words in the text) of the first item of the skill, it has the highest score, as its intensity reached (4,41) and its percentage weight reached (%88,3). The item (training students to be able to understand the hidden meaning of the text and the recognition of its aesthetic value) of the second item of the skill has gained the highest score which amounts to (4.33) with a percentage weight of (%86.6). The item (training the students on the use of educational aids related to the text, which may be pictures or phrases) of the third item of the skill has received the highest score, as its intensity reached (4.5) a percentage weight of (%90). According to these results, the researcher has recommended that students should be given enough time to be able to consider and understand the meaning of a text.